2012
DOI: 10.1038/ncomms1760
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 2 reverses tail-independent inactivation of kinesin-1

Abstract: Kinesin-1 is a plus-end microtubule-based motor, and defects in kinesin-based transport are linked to diseases including neurodegeneration. Kinesin can auto-inhibit via a head-tail interaction, but is believed to be active otherwise. Here we report a tail-independent inactivation of kinesin, reversible by the disease-relevant signaling protein, casein kinase 2 (CK2). The majority of initially active kinesin (native or tail-less) loses its ability to interact with microtubules in vitro, and CK2 reverses this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…One rationalization of these two observations is that, although kinesin inactivation/reactivation does not depend directly on kinesin's nucleotide state, CK2 causes a conformational change that both activates the motor and causes ADP release. We previously ruled out gross conformational changes: Inactivation occurs at the level of the single head, and no large change was observed in the sedimentation characteristics of the protein (13). Instead, we hypothesize that a smaller change occurs.…”
Section: Inactive Kinesin Undergoes a Conformational Change Resulting Inmentioning
confidence: 95%
See 4 more Smart Citations
“…One rationalization of these two observations is that, although kinesin inactivation/reactivation does not depend directly on kinesin's nucleotide state, CK2 causes a conformational change that both activates the motor and causes ADP release. We previously ruled out gross conformational changes: Inactivation occurs at the level of the single head, and no large change was observed in the sedimentation characteristics of the protein (13). Instead, we hypothesize that a smaller change occurs.…”
Section: Inactive Kinesin Undergoes a Conformational Change Resulting Inmentioning
confidence: 95%
“…Previously, we reported that when stored ("aged") on ice, kinesin went inactive over the course of a few hours and lost the ability to bind to microtubules (13). New experiments have confirmed such inactivation and have found that it is accelerated at higher temperatures as measured by both microtubule pelleting assays of dimers (Fig.…”
Section: Kinesin-1 Inactivation Is Accelerated At Physiologic Temperamentioning
confidence: 82%
See 3 more Smart Citations